2016
DOI: 10.1111/jcpt.12405
|View full text |Cite
|
Sign up to set email alerts
|

Partnered pharmacist charting on admission in the General Medical and Emergency Short-stay Unit - a cluster-randomised controlled trial in patients with complex medication regimens

Abstract: Partnering between medical staff and pharmacists to jointly chart initial medications on admission significantly reduced inpatient medication errors (including errors of high and extreme risk) among general medical and emergency short-stay patients with complex medication regimens or polypharmacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 16 publications
4
82
0
Order By: Relevance
“…The medication error rates in the setting of standard medical charting observed in the preintervention phase of this study were consistent with the previously reported randomised trial and previously published literature . Potential factors associated with such errors may be the multiple tasks provided by junior medical officers in the setting of an acute admission and the often limited history available from patients who are acutely unwell.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The medication error rates in the setting of standard medical charting observed in the preintervention phase of this study were consistent with the previously reported randomised trial and previously published literature . Potential factors associated with such errors may be the multiple tasks provided by junior medical officers in the setting of an acute admission and the often limited history available from patients who are acutely unwell.…”
Section: Discussionsupporting
confidence: 88%
“…Due to the large volume of errors identified and a previous randomised controlled trial demonstrating a reduction in high and extreme risk errors, a subset of 1 in 10 errors in the preintervention phase were randomly selected and assigned a risk rating by a blinded independent expert panel. The panel comprised a general physician, an emergency physician and a senior clinical pharmacist.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of pharmacists partnering with medical staff to manage medications for hospitalised patients have been demonstrated in multiple studies and include a significant reduction in medication errors. 5 However, there is still significant scope for these roles to be extended and for further roles to be developed.…”
Section: Improving Patient Care Today: More Timely Care and Expanded mentioning
confidence: 99%
“…Here the authors examine the inpatient chart before the introduction of the CPOE, the CPOE with the antimicrobial approval system, and then the CPOE alone -depending on which data was available in each time period. In a similar vein, the study by McInerney et al 5 of pharmacist interventions at an outpatient chemotherapy clinic used audits done at two separate times to investigate whether a new integrated cancer centre improved pharmacists' impact.…”
mentioning
confidence: 99%